Fractional radiofrequency in the treatment of skin aging: an evidence-based treatment protocol. (2nd January 2020) - Kleidona, Ileana Afroditi; Karypidis, Dimitrios; Lowe, Nicholas; Myers, Simon; Ghanem, Ali
ABSTRACT: Fractional radiofrequency (FRF) has recently emerged for the treatment of scars, cellulite and skin rejuvenation. The aim of this paper was to investigate the evidence behind its use in skin aging and evaluate efficacy, safety, and standardization of protocols. The literature was systematically searched and finally 25 full-text articles were included. Two were randomized controlled trials, 3 were comparative studies, and 20 were case series. Most studies were underpowered with low methodological quality. The participants had skin phototype I-VI with variable baseline severity of signs. Fractional radiofrequency using microneedles or electrode pins was performed on the face, neck, and décolletage. There was heterogeneity in outcomes measurement, but the efficacy of FRF was confirmed in all relevant studies. Mainly, the improvement of rhytides and skin tightening were reported. Mild to moderate pain, transient erythema and edema were the commonest adverse events. Hyperpigmentation was also noted in some cases. There was no consistency in the protocols used and in the description of procedures. A clinical impact score was created to assess the studies and to aid the generation of an evidence-based protocol for minimally invasive radiofrequency procedures. However, there is a need for large scale, well-designed trials to better investigate the efficacy and safety of FRF and to produce clear guidelines.